A cláusula compromissória como negócio jurídico = The arbitration clause as an legal contract - Barros, Maria Gabriella Dignani Schmidt de (2019)
Submitted by leitem@stj.jus.br (leitem@stj.jus.br) on 2019-08-09T17:47:53Z No. of bitstreams: 2 clausula_compromissoria_negocio_barros.pdf: 802564 bytes, checksum: ad397b37b621f869889a0802e14ef29b (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)